IMPLEMENTASI HILL CHIPER DAN STEGANOGRAFI GAMBAR BERBASIS WEB - Diva Insyarah Kausar; Nazwa Alviona; Khairatul Asyura; Elisabeth Dhea Chrysty Arnani Jikwa (JIKUM: Jurnal Ilmu Komputer, 2026)
Information security is an important requirement in digital communications, especially in webbased systems that are vulnerable to interception. This study aims to implement the Hill Cipher algorithm and image steganography as methods of securing web-based messages. The Hill Cipher is used to encrypt text messages, while the Least Significant Bit (LSB) method is applied to insert encrypted messages into digital images. The research methodology includes the stages of encryption, message insertion, extraction, and decryption. The test results show that messages are successfully encrypted and inserted into images without causing significant visual changes. This system enhances message security because messages are not only encrypted but also hidden. Thus, the combination of Hill Cipher and image steganography is effective as a web-based data security solution.